Dietary (poly)phenol intake is associated with cardiometabolic health parameters in adolescents - Emily P. Laveriano-Santos; Sara Castro-Barquero; Camila Arancibia-Riveros; Ruiz-León Ana María; Rosa Casas; Ramón Estruch; Patricia Bodega; Mercedes de Miguel; Amaya de Cos-Gandoy; Jesús Martínez-Gómez; Gloria Santos-Beneit; Juan M. Fernández-Alvira; et al. (Food Science and Human Wellness)
The protective role of (poly)phenols against metabolic disorders has been extensively studied in adults but not in adolescents. To assess associations of dietary (poly)phenols and their subclasses with cardiometabolic health parameters in adolescents. A cross-sectional study was conducted in 944 individuals aged 11–14 years enrolled in the SI! Program for Secondary Schools trial (NCT03504059). (Poly)phenol intake was assessed using semi-quantitative food frequency questionnaires and the Phenol-Explorer database. The measured cardiometabolic parameters were waist circumference (WC) age-sex Z-score, blood pressure (BP) age-sex Z-score, blood glucose (BG), triglycerides (TG), and high-density lipoprotein cholesterol (HDL-c). Multilevel mixed-effect linear regression models were applied to examine the association between (poly)phenol quintiles and cardiometabolic health parameters. Compared to the lowest quintile, adolescents in the highest quintile of total (poly)phenol intake had lower WC Z-scores, mean arterial pressure Z-scores, and HDL-c after multivariable adjustment. The WC Z-scores and HDL-c were lower in the highest quintile of flavonoid intake compared to the lowest quintile. The highest quintile of phenolic acid intake was associated with a lower WC Z-score and TG levels, and the highest quintile of stilbene intake with lower BG and TG, and with higher HDL-c compared to the lowest quintile. A higher intake of (poly)phenols, especially flavonoids, phenolic acids, and stilbenes, was associated with better cardiometabolic parameters in adolescents.